Pembiayaan Pendidikan Alternatif di Madrasah Tsanawiyah PPTQ Assalam Bandung Perspektif Analisis School Levy - Nenden Quratul Aini; Wia Adawiyah M; Ara Hidayat (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2020)
This research aims to describe education financing in Madrasah Tsanawiyah Pondok Pesantren Tahfiz Qur'an Assalaam Bandung using the School Levy analysis. School Levy is a concept of education financing in which the community (property tax) is set as the main source of the additional fund. This is a qualitative study. Data were collected by observations, in-depth interviews, and documentation then analyzed through data categorization and data interpretation. The results are 1) Alternative sources of education financing in MTs-PPTQ Assalaam were acquired through the funds from middle-high income communities in the form of zakat, infak, sedekah and Wakaf (ZISWAF); 2).The acquisition of the education financing sourced from ZISWAF is obtained in several ways. The first, Madrasa obligates students from the middle-high income family to pay certain amount of donation at the beginning of school year. The second, madrasa offers the parents to channel ZISWAF for educational financing tailored at the initial contract. Third, madrasa applies auction system for the Development Fund addressed for classrooms or other facilities improvement. 3) The Further utilization of this fund is used for madrasa’s development as well as facilities improvement, such as Wakaf land, Free Scholarship for 30% of orphans and duafa students, and as madrasa saving.